Endoscopic Removal of Third Ventricular Colloid Cyst: A Case Report - Nath, Haradhan Deb; Barua, Kanak Kanti; Islam, Md Monirul; Barua, Sudip; Mukherjee, Sudipta; Bhattacherjee, Rajib (Bangladesh Journal of Neurosurgery, 2020)
Third ventricular colloid cyst is slow-growing benign tumor comprising <1% of intracranial tumors. Previously it was removed by interhemispheric transcallosal or transcortical approach. Now a days, endoscopic removal of colloid cyst is a popular option because it is less invasive, panoramic view helps in total removal of tumor. Here we are reporting a 8 years old boy presented with occasional headache, vomiting, seizure and loss of consciousness for 3 months. Neuro-imaging revealed anterior third ventricular colloid cyst. We removed the tumor completely with rigid neuroendoscope which was confirmed by histopathology. After three months follow up patient was quiet healthy. Bang. J Neurosurgery 2020; 10(1): 119-122